UNCOVERING THE TRUTH: THE ABSENCE OF SANTA CLAUS RALLY IN U.S. STOCK MARKET RETURNS - Cinko, M; Avci, E (Journal of Current Practice in Accounting and Finance (JCPAF), 2023)
This research paper investigates the existence of the Santa Claus Rally in the U.S. stock market. The Santa Claus Rally is a phenomenon where stock market returns are significantly higher in the last five trading days of December and the first two trading days of January than the average returns of the remaining trading days of the year. Using data from January 2000 to December 2021, this study finds that the Santa Claus Rally does not exist in the U.S. stock market. The study also examines the existence of the Santa Claus Rally in two calendar sub-periods and during periods of economic expansions and recessions. The empirical results show that the Santa Claus Rally is not prevalent in the U.S. stock market during any of these sub-periods. The paper provides a review of the literature on stock market anomalies and concludes that publicly available academic research on the investigation of the Santa Claus Rally in stock returns is limited